Romania : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper discusses Romania's modeling monetary policy. A simple Forecasting and Policy Analysis System (FPAS) for Romania has been designed to help in the preparation of the IMF staff's forecasts and policy assessments. A major advantage of this approach is that it allows the systematic and rapid analysis of different policy options. The model embodies the key principle that, in an inflation-targeting framework, the role of monetary policy is to provide an anchor for inflation and inflation expectations. The development and calibration of this model is an ongoing process.